Mai cakap Penang / Azlina Mohd Mydin ... [et al.] - Mohd Mydin, Azlina; Wan Mohammad, Wan Anisha; Kechil, Rafizah; Johan, Elly Johana; Mohamed Yusoff, Syarifah Adilah (Unit Penerbitan Dan Publisiti JSKM, 2023)
Mai cakap Penang